Adjacent catchments with similar patterns of land use and climate have markedly different dissolved organic carbon concentration and runoff dynamics. Issue 3 (24th January 2013) - Oni, Stephen K.; Futter, Martyn N.; Molot, Lewis A.; Dillon, Peter J.
Abstract Temporal patterns in specific runoff, dissolved organic carbon concentrations [DOC] and fluxes were examined during two periods: 1994–1997 (period 1) and 2007–2009 (period 2) in five adjacent tributary catchments of Lake Simcoe, the largest lake in southern Ontario, Canada. The catchments displayed similar patterns of land use change with increases in urbanization (5–16%) and forest cover (0.2–4%) and declines in agriculture (4–8%) between 1994 and 2008. Climate in the catchments was similar; temperature increased slightly, but no significant change in precipitation was observed. Despite similar pattern of climate and land use, runoff responses and tributary [DOC] were different across the catchments. Following a very dry year (i.e. 1999), runoff increased steadily until the end of record. We observed increased variability in tributary [DOC] and higher DOC exports in period 2. This led to ~10% increase in [DOC] and a 13% increase in flux between the two study periods. Between the two periods, [DOC] increased by 15% in spring and 25% in summer, whereas flux increased by 17% in spring and 48% in summer. [DOC] was consistently higher in the growing (summer + autumn) than the dormant (winter + spring, minus spring melt months) seasons, but no unique pattern or simple linear flow/concentrations relationships existed. This suggests complex spatial and temporal pattern to runoff controls on DOC and flow dynamics in adjacent catchments. We therefore caution against extrapolating from monitored to unmonitored catchments. Copyright © 2012 John Wiley & Sons, Ltd.